EFESIENSI KERJA EFESIENSI KERJA ALAT MUAT KOMATSU PC 400 LC GUNA MEMENUHI KEBUTUHAN PRODUKSI STONE CRUSHER : EFESIENSI KERJA ALAT MUAT KOMATSU PC 400 LC GUNA MEMENUHI KEBUTUHAN PRODUKSI STONE CRUSHER - Bodian Davin Panggabean; Frans Simbol Tambing; Fandy Arapenta Ginting (JISTECH: Journal of Information Science and Technology, 2025)
PT. Semen Tonasa is a business entity engaged in the cement industry located in Biring Ere Village, Bungoro District, Pangkep Regency, South Sulawesi Province. PT Semen Tonasa currently has four operating factory units, namely Tonasa II, III, IV, and V units. In order to meet the planned production capacity, sufficient raw materials are needed, such as limestone in factory units II, III, IV, and V with a production capacity per unit of 1,200 tons/hour. So that the four stone crushers that must be met are 57,600 tons/day. Material retrieval is focused on the B8 mining location with a PC 400 LC loading tool. Based on the estimated calculation of the work production capacity of the equipment operated at the B8 mining location using two Komatsu PC 400 LC loading equipment, it is estimated at 274,268.52 tons/day with a work efficiency of 53%, it has been able to meet the production target to be distributed to all stone crusher processing equipment that is producing in the field, taking into account the delivery time and the number of transport equipment needed in the field. The design of production increase efforts to meet market demand targets can be done by reducing obstacles that occur in the field and increasing the number of transport equipment. So that the work efficiency of the loading equipment can be further optimized to meet the production needs of the crusher.